PriSUD-Nordic-Diagnosing and Treating Substance Use Disorders in the Prison Population: Protocol for a Mixed Methods Study - Bukten, Anne; Lokdam, Nicoline Toresen; Skjærvø, Ingeborg; Ugelvik, Thomas; Skurtveit, Svetlana; Gabrhelík, Roman; Skardhamar, Torbjørn; Lund, Ingunn Olea; Havnes, Ingrid Amalia; Rognli, Eline Borger; Chang, Zheng; Fazel, Seena; et al. (JMIR research protocols, 2022)
BACKGROUND: A large proportion of the prison population experiences substance use disorders (SUDs), which are associated with poor physical and mental health, social marginalization, and economic disadvantage. Despite the global situation characterized by the incarceration of large numbers of people with SUD and the health problems associated with SUD, people in prison are underrepresented in public health research. OBJECTIVE: The overall objective of the PriSUD (Diagnosing and Treating Substance Use Disorders in Prison)-Nordic project is to develop new knowledge that will contribute to better mental and physical health, improved quality of life, and better life expectancies among people with SUD in prison. METHODS: PriSUD-Nordic is based on a multidisciplinary mixed method approach, including the methodological perspectives of both quantitative and qualitative methods. The qualitative part includes ethnographic fieldwork and semistructured interviews. The quantitative part is a registry-based cohort study including national registry data from Norway, Denmark, and Sweden. The national prison cohorts will comprise approximately 500,000 individuals and include all people imprisoned in Norway, Sweden, and Demark during the period from 2000 to 2019. The project will investigate the prison population during three different time periods: before imprisonment, during imprisonment, and after release. RESULTS: PriSUD-Nordic was funded by The Research Council of Norway in December 2019, and funding started in 2020. Data collection is ongoing and will be completed in the first quarter of 2022. Data will be analyzed in spring 2022 and the results will be disseminated in 2022-2023. The PriSUD-Nordic project has formal ethical approval related to all work packages. CONCLUSIONS: PriSUD-Nordic will be the first research project to investigate the epidemiology and the lived experiences of people with SUD in the Nordic prison population. Successful research in this field will have the potential to identify significant areas of benefit and will have important implications for ongoing policy related to interventions for SUD in the prison population. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): DERR1-10.2196/35182.
Keywords: mixed methods; prison; treatment; criminal justice; harm reduction; epidemiology; substance use disorders